Socioeconomic profile of consumers and merchants fruit from Barra-BA (Research, Society and Development, 2020)
The objective identify the profile of consumers and traders of fruits of the city of Barra-BA, in order to generate informative data about fruit trade and consumption, with a view to proposing improvements and exploration of new niches in the fruit market city. The interviews were conducted by applying a socioeconomic questionnaire, applied to the retail trade of fruits and free markets in the city. 60.5% of consumers are female, 45% aged between 20 and 35 years. The frequency of buying fruit is weekly (62.5%), and most consumers (36%) spend on average R$ 21 to 30 per fruit purchase. For 69% the quality of the fruit partially meets their requirements. The bags stand out as the preferred place to buy fruit, representing 51%. Banana is the most consumed fruit by respondents (82%). 60.4% of traders do not buy fruits in the city because they can not find, being the city of Irecê-BA the main source of fruit supply (92.6%), which are transported in closed box trucks (46.4%) and trucks. with open body (43.9%). Postharvest loss is unanimous among traders, and most do not know how to solve the problem. The frequency of fruit consumer purchases is influenced by the logistics of merchants who usually renew shelves only once a week. Improvements in the city's fruit trade should be encouraged to better serve the population and prevent postharvest losses.